2017
DOI: 10.1075/sal.5.10nte
|View full text |Cite
|
Sign up to set email alerts
|

Language growth in child Emirati Arabic

Abstract: This study calculates developmental indices of language growth in Emirati Arabic based on a two-year longitudinal corpus collected from six Emirati children.1 The target indices include Mean Length of Utterance in morphemes and words (MLUm and MLUw), utterance-per-turn counts (UoT), type-token-ratio (TTR) and an index of vocabulary diversity (D). Spearman correlation tests show significant correlations between MLUm, MLUw and age. A slightly weaker correlation is found between age and D, while no correlation is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…[2], as cited in [3] norms for children between the ages of 3; 0-3; 5 shows total average of words 204.9 and total average of different words 92.5 TTR 0.45 while the mean score of the data collected from children between the ages of 2; 4 and 2; 9 is 140 and total average of different words 62.2 with TTR 0.447. In Emirati Arabic [17] found that there is no correlation between age and TTR was found in six children.…”
Section: Related Workmentioning
confidence: 89%
“…[2], as cited in [3] norms for children between the ages of 3; 0-3; 5 shows total average of words 204.9 and total average of different words 92.5 TTR 0.45 while the mean score of the data collected from children between the ages of 2; 4 and 2; 9 is 140 and total average of different words 62.2 with TTR 0.447. In Emirati Arabic [17] found that there is no correlation between age and TTR was found in six children.…”
Section: Related Workmentioning
confidence: 89%
“…The third corpus used in our experiments was the EMALAC corpus of Emirati Arabic child‐directed speech (Ntelitheos & Idrissi, ). The Emirati dialect of Arabic is the vernacular used in everyday interactions in the Gulf; like other dialects of Arabic, it is different than Modern Standard Arabic in a number of respects, including phonology, lexicon, and syntax.…”
Section: Methodsmentioning
confidence: 99%
“…MADAR (Bouamor et al, 2014) is an ongoing multi-dialect corpora covering 26 different cities and their corresponding dialects. Other efforts cover Emirati (Ntelitheos and Idrissi, 2017;Khalifa et al, 2018), Tunisian and Algerian (Zribi et al, 2015;Harrat et al, 2014), andYemeni andMoroccan (Al-Shargi et al, 2016).…”
Section: Dialectal Resourcesmentioning
confidence: 99%